2020
DOI: 10.1016/j.conbuildmat.2019.116917
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of steel reinforcements embedded in alkali activated ground granulated SiMn slag mortars

Abstract: The corrosion process of steel reinforcements embedded in alkali activated SiMn slag mortars was investigated. NaOH and waterglass were used as alkali activators of SiMn slag. The steel reinforced mortars were subjected to two aggressive environments: carbonation and chloride ingress. Carbonation progressed quicker for the binder activated with NaOH, decreasing the rate with the concentration. However, during the corrosion of the steels embedded in the mortars, both activators showed a similar behaviour. Morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…By adding metakaolin to the FA, not only is the geopolymerisation process enhanced, but also the porosity is decreased, hence improving the chloride ingress resistance [49,50]. However, the slags contribute to improved carbonation and chloride ingress resistance, as stated by Navarro et al [51]. Silica fume (SF) addition to OPC showed decreased chloride threshold values [52], but an increased chloride resistance performance was shown in different studies at the same time [53,54].…”
Section: Introductionmentioning
confidence: 95%
“…By adding metakaolin to the FA, not only is the geopolymerisation process enhanced, but also the porosity is decreased, hence improving the chloride ingress resistance [49,50]. However, the slags contribute to improved carbonation and chloride ingress resistance, as stated by Navarro et al [51]. Silica fume (SF) addition to OPC showed decreased chloride threshold values [52], but an increased chloride resistance performance was shown in different studies at the same time [53,54].…”
Section: Introductionmentioning
confidence: 95%
“…The database contains data for 125 GGBS-based AAC [6,8,; 12 FA-or MK-based AAC [8,[32][33][34][35][36]; 18 other AAC [36][37][38][39][40]; and 74 BCC [1,2,6,16,29,[41][42][43][44][45][46][47][48][49][50][51][52]. A plot of the SCM fractions of the binders of the materials (including the compounds dissolved in the activator solution as part of the binder in the calculation) is shown in Fig.…”
Section: Data Inventorymentioning
confidence: 99%
“…However, it is not constant that the higher the alkali concentration in all AAM systems, the lower the degree of carbonation. Conversely, Navarro et al [88] used water glass as activator, and the increased concentration of alkali activator led to an increase in the carbonation depth of SiMn slag-based AAMs. When using coal-based synthetic natural gas slag as a raw material and NaOH as an alkali activator, it was concluded that excessive alkali concentrations caused significant carbonation [89].…”
Section: Activators Compositionmentioning
confidence: 99%
“…Song et al [87] claimed that a higher concentration of alkali activator would contribute to a higher compressive strength of slag-based AAMs, but unfortunately, when the concentration of alkali activator is high, the compressive strength of slag-based AAMs would be lost more during the carbonation process. Navarro et al [88] produced AAMs using different concentrations of NaOH and Na 2 SiO 3 as activators, respectively, and found that the compressive and flexural strengths of all samples were increased after carbonation.…”
Section: Activators Compositionmentioning
confidence: 99%